Evaluation of the Effect of Topical Application of Melatonin on Dental Implant Success in Terms of Bone-Density Development "Clinical and Radiological Study" - أسعد منذر; حسن حازم; الدالي محمـد عصام (Latakia University Journal -Medical Sciences Series, 2021)
The aim of this study is to evaluate the effect of topical application of Melatonin in dental implants in terms of development of bone density. The sample consisted of 24 dental implants applied for 9 patients, each patient has received two implants at least . Each individual had their first implant with topical application of melatonin, and the second implant without melatonin application. Dental implants were evaluated at follow-up periods (one month, three months, six months) in terms of bone-density development. The research was conducted in the Oral Minor Surgery and Implantology Clinic in the Oral and Maxillofacial Department at Tishreen University Hospital. The results showed a difference between the two study groups with regards to the effect of topical application of melatonin on the success of dental implantation in terms of bone-density development throughout the three periods (one month, three months, six months), and this difference was in favor of the first group (with melatonin).